Correlation of Breakfast with Learning Concentration in Fourth Grade Elementary School - Alice Yeni Verawati Wote; Mardince Sasingan; M. M. Puji Nitis Kusumawati (Universitas Pendidikan Ganesha, 2022)
The students really need nutritional intake therefore breakfast is very important for them. Children who are accustomed to breakfast will have better abilities than children who are not accustomed to breakfast. Breakfast will stimulate growth and maximize children's abilities at school. This study aims to analyze the correlation of breakfast with the learning concentration of fourth grade elementary school students. The method used in this research is a survey method by conducting treatments in data collection, by distributing questionnaires, tests, structured interviews, and so on. This study uses a descriptive approach. The subjects in this study were 24 students including 11 male students and 13 female students. While the research stages are: 1) Documentation; 2) Questionnaire (Questionnaire preparation, Questionnaire Validity Test, Questionnaire Reliability Test. The instrument or measuring instrument used is the Likert Scale and the data analysis technique used is using